2012
DOI: 10.1128/jvi.00644-12
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and Mucosal Transmissibility of the R5-Tropic Simian/Human Immunodeficiency Virus SHIV AD8 in Rhesus Macaques: Implications for Use in Vaccine Studies

Abstract: There is an urgent need to develop new pathogenic R5 simian/human immunodeficiency viruses (SHIVs) for the evaluation of candidate anti-HIV vaccines in nonhuman primates. Here, we characterize swarm SHIV AD8 stocks, prepared from three infected rhesus macaques with documented immunodeficiency at the time of euthanasia, for their capacity to establish durable infections in macaques following inoculation by the intravenous (i.v.) or intrarectal (i.r.) route. All three viral stocks (SHIV AD8-CE8J , SHIV AD8-CK15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 54 publications
6
62
0
Order By: Relevance
“…We recently reported that only 3 of 19 monkeys inoculated with SHIV AD8 swarm stocks produced autologous neutralizing activity (13), and in the present study only 5 of 8 macaques inoculated with the SHIV AD8-EO molecular clone developed autologous NAbs ( Fig. 2A).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…We recently reported that only 3 of 19 monkeys inoculated with SHIV AD8 swarm stocks produced autologous neutralizing activity (13), and in the present study only 5 of 8 macaques inoculated with the SHIV AD8-EO molecular clone developed autologous NAbs ( Fig. 2A).…”
Section: Discussionmentioning
confidence: 65%
“…(5,000 or 500 TCID 50 ) and 7 by the intrarectal (5,000 or 1,000 TCID 50 ) routes. Similar to uncloned SHIV AD8 derivatives (13,14), the levels of set point viremia in macaques infected with the SHIV AD8-EO molecular clone varied widely (10 2 to >10 5 RNA copies/mL) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…It is important to consider the extensive mutation of the HIV-1 Env during monkey-to-monkey passages as frequently used SHIVs are adapted to the monkey in order to become pathogenic (Etemad-Moghadam et al, 2000;Hsu et al, 2003;Gautam et al, 2012). Boyd et al (2015) reported that SHIV adapted to utilize the monkey CD4 molecule, resulting in conformational changes that exposed epitopes in the variable regions.…”
Section: Discussionmentioning
confidence: 99%